A simple, efficient, and safe way of finding recurrent laryngeal nerve beneficial for PTC patients. Issue 19 (May 2020) - Yan, Shouyi; Xie, Chao; Zhao, Wenxin; Wang, Bo; Zhang, Liyong
Abstract: Background: More surgeons have known the importance of parathyroid grand and recurrent laryngeal nerve protection in the surgery, but there is still plenty of scope to improve the surgical techniques. This study aims at investigating whether the improved method of finding recurrent laryngeal nerve (RLN) can protect parathyroid grand and RLN. Methods: One hundred fifty-eight patients were enrolled and divided randomly into the test and control group according to different methods of finding RLN in the surgery. In the experimental group the author could quickly find the laryngeal recurrent nerve in the lower part of the neck and separate along the surface of the recurrent laryngeal nerve to the point where the recurrent laryngeal nerve gets into the larynx close to the thyroid gland named lateral approach, while in the control group the author severed the middle and lower thyroid vein and raised the lower thyroid pole to look for the RLN near the trachea by the blunt separation. Results: The author identified 152 and 159 parathyroid glands in the test and control group, respectively and there were a lower ratio of auto-transplantation and less operative time in the test group compared with that in the control group. The author also found that the parathyroid hormone level (1 day and 2 months) in the test group was higher than that in the control group. There were no differences in metastatic LN and recurrent laryngeal nerve palsy in the 2 groups. Conclusion: The improved method of finding RLN is a simple, efficient and safe way, and easy to implement.